The Scope of Auctions in the Presence of Downstream Interactions and Information Externalities - Onur A. Koska; Ilke Onur; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2015)
We scrutinize the scope of auctions in the presence of downstream interactions and information externalities by using the topical example of a firm acquisition. We show that no mechanism exists that allows an investor to acquire a low-cost firm under incomplete information: a separating auction implies adverse selection and relies substantially on commitment to allocation and transfer rules. A pooling auction serves as a commitment device against ex-post opportunistic behavior and alleviates adverse selection. It can earn the investor a higher expected payoff than a separating auction, even when consistency is required as to qualify for a sequential equilibrium.
Keywords: D44; D82; 330; takeover; auction; externality; incomplete information; commitment